Das Fach Gesellschaftslehre aus Akteur*innensicht: Eine qualitative Studie zu Chancen und Herausforderungen der gesellschaftswissenschaftlichen Fächerintegration an Gesamtschulen in NRW (k:ON - Kölner Online Journal für Lehrer*innenbildung, 2025)
The present article focuses on the subject of GL and the associated opportunities and challenges of integrating social science subjects in comprehensive schools in NRW. Professors and teachers were interviewed for this purpose. The main outcome was the creation of a model, which identified a need for action on various levels. This is deemed necessary to overcome the current status quo and its related challenges and to unlock the potential of the subject.
Keywords: Social studies; Interdisciplinarity; opportunities and challenges; need for action; Reality complexity; teacher education